Application of Fuzzy AHP for Ranking Critical Success Factors for the Successful Implementation of Lean Production Technique - Aikhuele, Daniel Osezua; Souleman, Fathi S.; Amir, Azizi (AENSI Publishing, 2014)
The implementation of lean production techniques in a product assembly environment depends on a numbers of factors and these factors constitute the backbone for the successful implementation of the lean technique. Although, many research efforts, both theoretical and practical studies have been made over the year on the identification and evaluation of the critical success factors (CSFs) for lean implementation, but very little or less effort has been devoted to evaluating the actual contribution of each of these factors to the overall success of the lean implementation program. This study therefore presents a framework for ranking and evaluating the contribution of these critical success factors in the order in which they accounts for the successful implementation of lean production techniques using Fuzzy Analytic Hierarchy Process (FAHP) approach.